Análise do saneamento ambiental no bairro da Cidade Nova, município de Ananindeua - PA - SILVA, Fabrício Martins (2020)
The present study aims to highlight through some important environmental variables (sanitary sewage, selective collection, water supply system, flooding points) the basic sanitation services in City New neighborhood, Ananindeua - PA, Metropolitan Region of Belém, Northeast of the state of Pará. This analysis included bibliographic and documentary information, fieldwork for photographic recording and georeferencing of the variables mentioned, as well as the use of mobile applications. The systematization of the collected information and its representations are represented in maps and graphs. The results show that the neighborhood presents its flat terrain and confirms that the sanitation problems come from the precarious infrastructures and/or absence or inefficiency of public management that the municipality as a whole presents, putting itself in second to last in the ranking of the best Brazilian cities. To live. Less than 1% of the population is served by basic services that are rights guaranteed in the country's legal system. In recent years, the neighborhood has shown strong demographic growth, reflecting on the urbanization that followed in a disorderly and unplanned manner, especially on the environment. The study also demonstrated the need for completion of unfinished works. And environmental management should start from a full diagnosis of the problems from local studies related to drainage and solid waste collection. These actions could reduce risks of contact with contaminated water and improve the quality of life of the population.